Ethanolic Neem (Azadirachta indica) Leaf Extract Prevents Growth of MCF-7 and HeLa Cells and Potentiates the Therapeutic Index of Cisplatin. (30th January 2014) - Sharma, Chhavi; Vas, Andrea J.; Goala, Payal; Gheewala, Taher M.; Rizvi, Tahir A.; Hussain, Arif
Abstract : The present study was designed to gain insight into the antiproliferative activity of ethanolic neem leaves extract (ENLE) alone or in combination with cisplatin by cell viability assay on human breast (MCF-7) and cervical (HeLa) cancer cells. Nuclear morphological examination and cell cycle analysis were performed to determine the mode of cell death. Further, to identify its molecular targets, the expression of genes involved in apoptosis, cell cycle progression, and drug metabolism was analyzed by RT-PCR. Treatment of MCF-7, HeLa, and normal cells with ENLE differentially suppressed the growth of cancer cells in a dose- and time-dependent manner through apoptosis. Additionally, lower dose combinations of ENLE with cisplatin resulted in synergistic growth inhibition of these cells compared to the individual drugs (combination index <1). ENLE significantly modulated the expression of bax, cyclin D1, and cytochrome P450 monooxygenases (CYP 1A1 and CYP 1A2) in a time-dependent manner in these cells. Conclusively, these results emphasize the chemopreventive ability of neem alone or in combination with chemotherapeutic treatment to reduce the cytotoxic effects on normal cells, while potentiating their efficacy at lower doses. Thus, neem may be a prospective therapeutic agent to combat gynecological cancers.